2013
DOI: 10.1088/0004-637x/779/1/83
|View full text |Cite
|
Sign up to set email alerts
|

Electron Cyclotron Maser Emission in Coronal Arches and Solar Radio Type v Bursts

Abstract: Solar radio type V bursts were classified as a special spectral class based on their moderately long duration, wide bandwidth, and sense of polarization opposite of associated type III bursts. However, type V bursts are also closely related to the preceding type III bursts. They have an approximately equal source height and the same dispersion of position with frequency. Electron cyclotron maser (ECM) instability driven by beam electrons has been used to explain type III bursts in recent years. We propose ECM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…The starting times of the radio burst were consistent with the HXR peak times of the flare. Since the type III radio emissions result from the cyclotron maser instability of the nonthermal electron beams that are accelerated and ejected into the interplanetary space along open magnetic field lines during the flare (Tang et al 2013), the type III radio burst observed by STEREO and WIND provides indirect and supplementary evidence that open magnetic field lines exist near the flare site.…”
Section: Resultsmentioning
confidence: 99%
“…The starting times of the radio burst were consistent with the HXR peak times of the flare. Since the type III radio emissions result from the cyclotron maser instability of the nonthermal electron beams that are accelerated and ejected into the interplanetary space along open magnetic field lines during the flare (Tang et al 2013), the type III radio burst observed by STEREO and WIND provides indirect and supplementary evidence that open magnetic field lines exist near the flare site.…”
Section: Resultsmentioning
confidence: 99%
“…Authors also pointed out that growth rates of X mode are considerably higher than those of O mode. Although other works were carried out to explore this new ECME via introducing a loss cone or temperature anisotropy in the distribution function, results always suggest that the fastest growth mode is the X mode (Tang & Wu 2009;Tang et al 2011Tang et al , 2013.…”
Section: Discussionmentioning
confidence: 99%
“…One explanation of type V emission is low energy electrons travelling along different magnetic field lines or a variation of the beaming of emission changes the position of the centroids . Another explanation given for type V emission is the electron-cyclotron maser instability (Winglee & Dulk, 1986;Tang et al, 2013).…”
Section: Type V Burstsmentioning
confidence: 99%